Uma proposta de arquitetura para gestão de Atas de Registro de Preços - Magalhães, Fábio Arruda (2022)
The purchasing and contracting processes are essential to meet the operational needs of any organization, thus enabling it to reach its goals. This reality is also common to all the agencies that make up the Public Administration. Unlike the private sector, public purchasing and contracting must be carried out through competitive biddings, ensuring wide disclosure and transparency of information. Over the years, the Brazilian legislation dealing with this issue has been improved several times. The electronic auction and the Price Registration System (SRP), for example, were important instruments that contributed to the modernization of this important process. The supply contracts (Acts of Price Registry) that have their origin in the electronic bidding conducted by SRP require an efficient information management process from public managers, so that the public budget is executed optimally. However, some information related to this domain, contained in the System for the Administration of General Services (SIASG), are dispersed in different modules, favoring the use of parallel controls, prone to problems such as redundancy and inconsistency in the data. Without a trusted place to consult this information, managers' decision-making can be compromised. Although there is literature on government procurement, there is still little focus from a software architecture perspective, which is why no solution to the problem has been located. In this master dissertation, we present the specification, design, and evaluation of a software architecture that aims to structure the essential information for the management of price registration minutes, which aims to contribute to the decision-making process related to the application of budget resources. The execution of these steps was based on a process model experienced by the industry, with some adaptations. Design Science Research (DSR) was the research method that guided the conception of the proposed artifact. The results of the evaluations show that future instances of the proposed architecture have the potential to solve the problems identified.